2016
DOI: 10.1016/j.csda.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Fast computation of reconciled forecasts for hierarchical and grouped time series

Abstract: We describe some fast algorithms for reconciling large collections of time series forecasts with aggregation constraints. The constraints arise due to the need for forecasts of collections of time series with hierarchical or grouped structures to add up in the same manner as the observed time series. We show that the least squares approach to reconciling hierarchical forecasts can be extended to more general non-hierarchical groups of time series, and that the computations can be handled efficiently by exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 10 publications
0
80
0
2
Order By: Relevance
“…The corresponding GLS may be too large to solve without special numerical methods. Hyndman et al (2011, section 5) discuss some potential remedies, and Hyndman et al (2014a) have recently proposed a fast recursive approach for specific hierarchy topologies.…”
Section: Reconciliation Of Forecastsmentioning
confidence: 99%
“…The corresponding GLS may be too large to solve without special numerical methods. Hyndman et al (2011, section 5) discuss some potential remedies, and Hyndman et al (2014a) have recently proposed a fast recursive approach for specific hierarchy topologies.…”
Section: Reconciliation Of Forecastsmentioning
confidence: 99%
“…The new combination approach proposed in Athanasopoulos et al (2009) andHyndman et al (2011) considers smaller hierarchies with less than four levels, while hierarchies with millions of time series at the lowest level are discussed in Hyndman et al (2014). Starting point of this approach is to forecast all time series at all (aggregate and disaggregate) levels first.…”
Section: Optimal Forecast Combination For Hierarchical Time Seriesmentioning
confidence: 99%
“…On the other hand, it is possible that assumption (1) becomes less and less adequate, in particular for a longer and longer forecast 9 horizon. Hyndman et al (2016) proposed a GLS estimator, where the elements of Σ + h are set to the inverse of the variances of the base forecasts, Var(y n+1 − y n+1|n ). Note that we use the one-step-ahead forecast variances, not the h-step-ahead forecast variances.…”
Section: Optimal Combinationmentioning
confidence: 99%
“…This method is referred to as the middle-out method. Hyndman et al (2011) andHyndman, Lee andWang (2016) proposed an optimal combination method, where base forecasts are obtained independently for all series at all levels of the hierarchy and then a linear regression model is used with an ordinary least squares (OLS) or a generalized least squares (GLS) estimator to optimally combine and reconcile these forecasts. They showed that the revised forecasts do not only add up across the hierarchy, but they are also unbiased and have minimum variance amongst all combined forecasts under some simple assumptions (Hyndman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%